The Australian Green Consumer Guide : Choosing Products for a Healthier Home, Planet and Bank Balance. - Ha, Tanya (University of NSW Press, 2007)
There has never been a greater need for an Australian green consumer guide to help people make informed choices about the products they buy. Tanya Ha responds to the shift in public debate about climate change toward actively seeking solutions with a practical guide that encourages consumers to become informed, get involved and to vote with their dollar. Packed with answers - practical tips and advice to help the reader make a real difference in their own lives - The Australian Green Consumer Guide is an essential, non-judgemental guide to making more ecologically sound consumer choices, wheth.